Noël sur le balcon/ Hold The Color : Paulina Olowska / Lucy McKenzie. - McKenzie, Lucy; Urbaschek, Stephan; Okiishi, Ken (München : Kunstverlag Ingvild Goetz, 2007)
Olowska, Paulina
Noël sur le balcon / Hold the Color. Paulina Olowska /Lucy McKenzie, Sammlung Goetz, Munchen, 26 maart tot 4 augustus 2007
boek
Keywords: McKenzie, Lucy